2022
DOI: 10.3390/su14063570
|View full text |Cite
|
Sign up to set email alerts
|

Outdoor Space Quality Mapping by Combining Accessibility, Openness, and Microclimate: A Case Study in a Neighborhood Park in Shanghai, China

Abstract: The vitality of outdoor space is largely determined by its quality, which encompasses many factors such as traffic accessibility, openness, microclimate, etc. Creating space with high quality can attract more visitors and contribute to urban vitality and sustainability. Visualization of quality distribution can aid the design and management of high-quality outdoor spaces. In this study, we developed a method for generating an integrated outdoor space quality map by normalizing, weighting, and summing up the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Devising spatial prototypes is also essential because they can play a determining role in the perceived comfort of microclimates [ 31 ], which our general investigation of break spaces revealed to be an important influence upon the willingness of students to go outside. Accessibility, openness, and the microclimate have been combined to describe the quality of outdoor spaces in other studies [ 24 ]. All these factors are related to spatial characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Devising spatial prototypes is also essential because they can play a determining role in the perceived comfort of microclimates [ 31 ], which our general investigation of break spaces revealed to be an important influence upon the willingness of students to go outside. Accessibility, openness, and the microclimate have been combined to describe the quality of outdoor spaces in other studies [ 24 ]. All these factors are related to spatial characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…To explore the relationship between the spatial prototypes and their restorative quality, it was essential to be able to quantify their spatial features. A detailed literature survey revealed that scale, location, and spatial patterns were the most accessible measures for describing outdoor spaces [ 12 , 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Enclosure refers to the degree to which buildings or other physical barriers surround a UV. The enclosure can affect the microclimate of an urban void, as well as its accessibility and visibility (Tao et al, 2022).…”
Section: Evaluation Of Urban Voids Based On Ecological Criteriamentioning
confidence: 99%